2007
DOI: 10.1007/s11695-007-9006-5
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy — A Restrictive Procedure?

Abstract: This study indicates that following SG, the stomach empties its contents rapidly into the small intestine and symptoms of vomiting after eating (characteristic of restrictive procedures) are either absent or very mild. Therefore, the term 'restrictive' is possibly ill-advised for this new bariatric operation. It remains for other mechanisms of energy intake reduction, such as intestinal distension and satiety signals through gut hormones to be investigated, to comprehensively explain precisely how this 'food l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
199
2
25

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(244 citation statements)
references
References 20 publications
(30 reference statements)
12
199
2
25
Order By: Relevance
“…Its discovery has shed new light on many physiological functions. Among the several actions of this peptide in the human body, ranging from its involvement in the regulation of the immune and cardiovascular systems to the up-regulation of insulin-like growth factor, it has a dominant role in the gastrointestinal system, with involvement in gastric emptying and intestinal motility (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Its discovery has shed new light on many physiological functions. Among the several actions of this peptide in the human body, ranging from its involvement in the regulation of the immune and cardiovascular systems to the up-regulation of insulin-like growth factor, it has a dominant role in the gastrointestinal system, with involvement in gastric emptying and intestinal motility (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Leaks and bleeding represent the most feared complications and the most frequently reported causes of death after LSG. Reported leak rates range from 0.7 to 5.3% [24,41,[44][45][46]50]. Esophageal stenting (endoluminal technique) is an effective and new strategy for treatment of gastric fistula, and may be performed safely in a patient with leak of the staple line following sleeve or re-sleeve gastrectomy (for weight regain) with or without BPD-DS [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Hould et al [23] reported a hastened gastric emptying in patients who underwent BPD-DS as compared to controls and BPD. Recently, Melissas et al [24] reported the results of antrum functionality in patients who underwent SG. Those results have added some important details to the mechanism involved in SG to achieve weight loss.…”
Section: Mechanism Of Action Of Sleeve Gastrec-tomymentioning
confidence: 99%
“…An increased risk of hematoma developing and abscess formation is found as a result. Early bleeding through drains or NG tube is called a sentinel bleed and it usually can occur within hours of surgery [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%